Pengaruh Game Online terhadap Motivasi Belajar Peserta Didik SMAN 1 Adonara Tengah, Desa Kenotan, Kecamatan Adonara Tengah, Kabupaten Flores Timur Tahun Pelajaran 2022/2023 - Veronika Frumentia T. Mawar; Imelda Oliva Wissang; Yoakim Yolanda Mario Leu (Social Science Academic, 2023)
The purpose of this study was to describe the effect of online games on the learning motivation of student of class X IPS of IPA SMAN 1 Adonara Tengah, Kenotan Village, Adonara Tengah, District, East Flores Regency for the 2022/2023 Academic Year. The problem in this study is how online games influence the learning motivation of student in class X IPA and class X IPS of SMAN 1 Adonara Tengah, Kenotan Village, Adonara Tengah District, East Flores Regency. The population in this study were class X IPA and X IPS of SMAN 1 Adoanara Tengah Kenotan Village, Adonara Tengah Discrict, East Flores Regency for the 2022/2023 academic year, which consisted of 40 student, so the sample was taken from the entire population, namely 40 students. The instruments used in this study were observation and quistionnaires, where the questionnaire contained 20 question items. The data analysis technique used in this study is the product moment correlation formula with the result of the correlation coefficient between online games on student learning motivation ( Rxy ) of 0.3 which shows that there is an influence between online games on student learning motivation carrelated significantly at a significant level of 9%. Then it was tested for significance using the “t” test form;;ula. For a real rate of 0.03, based on the calculation above, tcount = 1,93 while t table = 1. 684 tcount > t table, namely 1.93 > 1. 684, Ha is accepted, Ho is rejected. This shows that between variable X and variable Y it can be concluded that there is and influence of online games on student learning motivation at SMAN 1 Adonara Tengah Kenotan Village, Adonara Tengah District, Esat Flores Regency, in the 2022/2023 Academic Year. So from the calculations obtained above, the effect of online games on student learning motivation SMAN 1 Adonara Tengah, Kenotan Village, Adonara Tengah Discrict, East Flores Regency for the 2022/2023 academic year 9%.